Penyelidikan Zona Longsor dengan Metode Resistivitas dan Analisis Stabilitas Lereng untuk Mitigasi Bencana Tanah Longsor - Muwardi Sutasoma; Adi Susilo; Eko Andi Suryo (Department of Physics, Sebelas Maret University, 2017)
Research using geoelectric resistivity dipole-dipole configuration and slope stability analysis has been done in the area Jawar, District Dampit to find out the sliding plane landslide, landslide direction and factor of safety. Tracks Retrieval of data by the method of geoelectric resistivity as much as 5 tracks with the direction of the southeast to the northwest three tracks with a length of 100 m - 200 m and southwest to northeast as many as two passes with a length of 200-300 m. While the slope stability analysis performed topographic map data retrieval and data collection sondir and boring. Based on the analysis of the lithology of the study area using resistivity geoelectric method shows three layers of soil is clay (the top layer), tuff (middle layer) and basalt and lava (bottom layer). sliding plane landslide area is in the boundary between the layers of clay and tuff (a depth of 10.5 m). Based on the results of data processing of 3D resistivity geoelectric, landslide direction is southeast. Safety factor value of the security research area based slope stability analysis is 1.015. This value indicates that this area is prone to landslides.